2021
DOI: 10.3390/ijerph18041484
|View full text |Cite
|
Sign up to set email alerts
|

Transition to Multidisciplinary Pediatric Telerehabilitation during the COVID-19 Pandemic: Strategy Development and Implementation

Abstract: Telerehabilitation offers a unique solution for continuity of care in pediatric rehabilitation under physical distancing. The major aims of this study were to: (1) describe the development of telerehabilitation usage guidelines in a large hospital in Israel, and to (2) evaluate the implementation of telerehabilitation from the perspectives of healthcare practitioners and families. An expert focus group developed guidelines which were disseminated to multidisciplinary clinicians. Following sessions, clinicians … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 33 publications
0
36
0
4
Order By: Relevance
“…Similar to global trends, Israel also changed its use of telehealth services. A study carried out by a pediatric rehabilitation hospital in Israel [ 23 ] demonstrated how the number of tele-rehabilitation sessions increased to 110 over a five-week period in late March to the end of April 2020. They reported that although both children (mean age = 11 years) and therapists were able to maintain a therapeutic “connection” during this period, other rehabilitation goals were perceived to be less achievable, specifically in physical and occupational therapy.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Similar to global trends, Israel also changed its use of telehealth services. A study carried out by a pediatric rehabilitation hospital in Israel [ 23 ] demonstrated how the number of tele-rehabilitation sessions increased to 110 over a five-week period in late March to the end of April 2020. They reported that although both children (mean age = 11 years) and therapists were able to maintain a therapeutic “connection” during this period, other rehabilitation goals were perceived to be less achievable, specifically in physical and occupational therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-COVID, a lot of key information was shared between therapists during those breaks, information that was not necessarily documented in the electronic medical record. Similar to other global and local tele-rehabilitation settings [ 22 , 23 ] particular attention is now focused on how information is documented and shared between therapists and with families to better meet their needs for both remote and in-person therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, kinematic measurement recorded via objects such as instrumented spoons may provide assessment of movement remotely. Existing telehealth applications are often limited in their ability to accurately assess movement quality, specifically in children [29]. Thus, kinematic analysis of self-feeding may be a valuable addition to existing measures of movement quality.…”
Section: Discussionmentioning
confidence: 99%